2005
DOI: 10.1158/1078-0432.ccr-05-0459
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Treatment with Three Thrombospondin-1 Type 1 Repeats versus Gemcitabine in an Orthotopic Human Pancreatic Cancer Model

Abstract: Purpose: In this study, we investigated the antitumor efficacy of thrombospondin-1three type 1 repeats (3TSR), the antiangiogenic domain of thrombospondin-1, in comparison and in combination with gemcitabine, in an orthotopic pancreatic cancer model. Experimental Design: Human pancreatic cancer cells were injected into the pancreas of severe combined immunodeficient mice. The animals were treated with 3TSR, gemcitabine, 3TSR plus gemcitabine, or vehicle for 3 weeks. Subsequently, the effects of 3TSR and/or gem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 42 publications
2
23
1
Order By: Relevance
“…Although several studies have targeted the VEGF family in ovarian cancer (15)(16)(17)(18), another effective approach for the treatment of various cancers are peptides derived from the TSR antiangiogenic domain of TSP-1 (19). Numerous studies have shown the antiangiogenic and antitumor effects of 3TSR (20)(21)(22) and ABT-510 (11,23,24) and have shown safety and efficacy in animal and human studies (12,13,25,26). We have previously evaluated ABT-510 in the treatment of EOC and reported decreased tumor burden as well as an increase in the uptake of the chemotherapy drugs cisplatin and paclitaxel through vascular normalization (8).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have targeted the VEGF family in ovarian cancer (15)(16)(17)(18), another effective approach for the treatment of various cancers are peptides derived from the TSR antiangiogenic domain of TSP-1 (19). Numerous studies have shown the antiangiogenic and antitumor effects of 3TSR (20)(21)(22) and ABT-510 (11,23,24) and have shown safety and efficacy in animal and human studies (12,13,25,26). We have previously evaluated ABT-510 in the treatment of EOC and reported decreased tumor burden as well as an increase in the uptake of the chemotherapy drugs cisplatin and paclitaxel through vascular normalization (8).…”
Section: Discussionmentioning
confidence: 99%
“…The schedules used are also highly variable, although typically these studies involved giving the AIAs and chemotherapeutic drugs over the same time period. What is clear is that the majority of studies reported an increased benefit of the combination approach, although in a few examples no additional benefit was found (164)(165)(166).…”
Section: Combining Vtas With Other Therapiesmentioning
confidence: 99%
“…66 In most cases, the inhibition of tumor growth by 3TSR is due to inhibition of angiogenesis, with no direct effects on the tumor cells. However, 3TSR reportedly inhibits the growth of brain and ovarian cancer cells through direct interaction with CD36, which is expressed on the tumor cells.…”
mentioning
confidence: 99%